A Detailed Step-by-Step Description of the Measurement of Absolute Inductances of Permanent Magnet Synchronous Machines - Kellner, Sven; Piepenbreier, Bernhard (International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, 2012)
This paper presents a detailed description of the measurement process of the absolute in ductances L,i and Lq of permanent magnet synchronous machines (PMSMs). Knowledge of the inductances of the PMSMs is very important for closed loop control of the machine. The measurement is based on the well known linearized PMSM equations [1]. Both the theoretical background of the inductance measurement such as the influences of iron losses [2,3,4.5] and the actual realization of the measurement process itself are discussed in the paper. While the test bench setup can prepared quickly and easily, the calculation of the inductances based on the measurement results is fairly complex. The paper shows the whole measurement process in detail. © VDE Verlag GMBH - Berlin.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.adetai